Assessing the Diets of Young Children and Adolescents in India: Challenges and Opportunities - Locks, Lindsey M.; Shah, Miloni; Bhaise, Shilpa; Hibberd, Patricia L.; Patel, Archana (Frontiers in Pediatrics, 2022)
Sustainably addressing the crisis of undernutrition for children and adolescents in underserved and resource-limited communities will require, among other investments, interventions aimed at optimizing the diets of these vulnerable populations. However, to date, there are substantial global gaps in the collection of dietary data in children and adolescents. This review summarizes the challenges and opportunities in assessing diet among children and adolescents in India. National surveys in India identify the scale of the triple burden of malnutrition (undernutrition, micronutrient deficiencies and overnutrition) in children and adolescents and assess key nutrition and food security indicators for making informed policy decisions. However, national surveys do not collect data on diet, instead relying on anthropometry, biomarkers of micronutrient deficiencies, and summary measures of diet, such as the WHO infant and young child feeding indicators. Sub-national surveys and the scientific literature fill important gaps in describing the nutrient intakes of children and adolescents in India; however large gaps remain. Future research can be improved by investments in infrastructure to streamline the assessment of diet in India. Challenges confronting the collection and analysis of high-quality dietary data occur in both the data collection and analysis phases. Common methods for assessing diets in low-resource settings – such as 24-hour recalls and food frequency questionnaires are particularly challenging to implement well in young children and adolescents due to motivation and memory issues in young respondents as well as the consumption of meals away from parents, limiting the use of parental recall. Furthermore, analysis of dietary data is hindered by the lack of affordable, accessible software for dietary data analysis relevant to the diversity in Indian diets. New technologies can address some of these challenges, but to date, there are no platforms designed for large-scale dietary assessment in India. Public and private sector investment in dietary assessment, as well as collaboration of researchers and the creation of open-source platforms for the sharing of data inputs (local food lists, recipe databases, etc.) will be essential to build infrastructure to better understand the diets of children and adolescents in India and improve dietary interventions in these target groups.